La caducidad tributaria en el impuesto a la renta: aplicación práctica en la legislación ecuatoriana - Morales Castro, Samuel (2018)
The Ecuadorian tax system has tried to guarantee its normative excellence by promulgating, reforming and improving the legislation of the matter in order to optimize taxation; in such a way that, the present work with seat in the constitutional legislation, investigates, through a practical case, the efficiency of the tributary legal relation, when confronting in diametrically opposed poles, the Internal Revenue Service, as owner of the relation legal entity and the company as a legal entity and subject obliged to make the corresponding payments of income tax. In this channel, the work focuses on the tax expiration, as an institution of law that prescribes the passage of time before the inaction of the owner, until its total decline and loss, leading consequently to the impossibility of collection or what is equal to the exemption of the taxpayer's payment, by virtue of the principle of legal security. These courses generate an analysis based on expiration, both in legislation and in Ecuadorian jurisprudence, when applied to business dynamics in everyday legal transactions.